Refining fibroblast-to-cardiomyocyte transdifferentiation protocols to explore emergent self-organization in cardiac cultures - Elena Turchaninova; Sofya Robustova; Sandaara Kovalenko; Vitalii Dzhabrailov; Aleria Dolgodvorova; Serafima Romanova; Dmitriy Zybin; Mikhail Popov; Alsu Miftakhova; Sheida Frolova; Mikhail Slotvitsky; Alexander Romanov; et al. (PLoS ONE, 2026)
Fibrotic scars post-myocardial infarction disrupt cardiac conduction, causing arrhythmias. We developed a minimized 4-component cocktail (CHIR99021/BMP4/Activin A/IWP2) for efficient fibroblast-to-cardiomyocyte transdifferentiation. The use of the developed four-component protocol enables the generation of cells with electrical excitability and key cardiomyocyte markers, as evidenced by 56–83% of cells expressing α-actinin. This level of partial reprogramming of fibroblast cells into cardiac cells is sufficient to restore cardiac tissue conductivity, with an efficiency that exceeds the critical percolation threshold. Systemic delivery of components is safe, but requires further optimization, which will open up opportunities for localized delivery through smart substrates and combinations with cell therapy. Minimization of the transdifferentiation cocktail is not a compromise, but a strategic advantage that provides an optimal balance between functional efficiency and clinical applicability, including safety, delivery, and manufacturing.